Cytomegalovirus proteins. I. Polypeptides of virions and dense bodies. - Fiala, M (1976)
Cytomegalovirus virions and dense bodies were purified by sucrose velocity and equilibrium centrifugation from the medium of fibroblasts infected with the strain AD169. The final virus preparations were purified more than 228-fold with respect to cellular proteins as determined by double-isotopic labeling and at least 1,600-fold on the basis of changes in the ratio of total protein to virus particles. The protein content of purified particles approximated that found for purified preparations of other herpesviruses. Twenty polypeptides ranging from 22,000 to greater than 230,000 molecular weight were detected in purified virus preparations by sodium dodecyl sulfate-polyacrylamide gel electrophoresis. Polypeptides of virions and dense bodies were allocated on the basis of analyses of preparations containing differing percentages of virions and dense bodies. Six polypeptides were represented predominantly or exclusively in virions, and four polypeptides were represented predominantly or exclusively in dense bodies, whereas the remainder appeared to be shared by both types of particles. Four polypeptides were glycosylated, and at least three of these appeared to be shared by both particles. Four polypeptides were glycosylated, and at least three of these appeared to be shared by both particle types. The protein composition of cytomegalovirus differs profoundly from that of herpes simplex virus.